Combined genomic and transcriptomic analysis reveals the contribution of tandem duplication genes to low-temperature adaptation in perennial ryegrass - Wang, Wei; Li, Xiaoning; Fan, Shugao; He, Yang; Wei, Meng; Wang, Jiayi; Yin, Yanling; Liu, Yanfeng (Frontiers in Plant Science, 2023)
Perennial ryegrass (Lolium perenne L.) is an agronomically important cool-season grass species that is widely used as forage for ruminant animal production and cultivated in temperate regions for the establishment of lawns. However, the underlying genetic mechanism of the response of L. perenne to low temperature is still unclear. In the present study, we performed a comprehensive study and identified 3,770 tandem duplication genes (TDGs) in L. perenne, and evolutionary analysis revealed that L. perenne might have undergone a duplication event approximately 7.69 Mya. GO and KEGG pathway functional analyses revealed that these TDGs were mainly enriched in photosynthesis, hormone-mediated signaling pathways and responses to various stresses, suggesting that TDGs contribute to the environmental adaptability of L. perenne. In addition, the expression profile analysis revealed that the expression levels of TDGs were highly conserved and significantly lower than those of all genes in different tissues, while the frequency of differentially expressed genes (DEGs) from TDGs was much higher than that of DEGs from all genes in response to low-temperature stress. Finally, in-depth analysis of the important and expanded gene family indicated that the members of the ELIP subfamily could rapidly respond to low temperature and persistently maintain higher expression levels during all low temperature stress time points, suggesting that ELIPs most likely mediate low temperature responses and help to facilitate adaptation to low temperature in L. perenne. Our results provide evidence for the genetic underpinning of low-temperature adaptation and valuable resources for practical application and genetic improvement for stress resistance in L. perenne.